Close and Connected: The Effects of Proximity and Social Ties on Citizen Opposition to Electricity Transmission Lines. Issue 5 (June 2018) - Nelson, Hal T.; Swanson, Brian; Cain, Nicholas L.
To meet reliability and renewable energy goals, new high-voltage transmission line (HVTL) projects are being built in the United States and worldwide. The siting of HVTLs, often considered a locally unwanted land use (LULU), can be difficult due to the negative externalities they create. Based on a survey of 358 residents of Chino Hills, California, we find that respondents' main concerns in regard to an HVTL project were health risks and harm to property values. Regression modeling finds that citizens who live close to the project, and are more connected to each other, are more likely to oppose the project. Psychosocial perceptions of project risks are also an important predictor of opposition. A high level of perceived risk moderates the effects of distance on opposition attitudes and behaviors. Trust in the project sponsor is a significant independent predictor of opposition, and moderates the relationship between distance and opposition.